“Mencari Pemimpin Yang Cerdas Emosi Dan Spiritual” (Sebuah Tinjauan Atas Problem KPK-POLRI) - Max L. Taolin (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2014)
KPK and POLRI Problem as issue which there are many get attention of Indonesian government, people and extent society. To settle that problem impact acts extended needful leadership which have emotional and spiritual quotient. Leadership which have emotional and spiritual quotient has tall consciousness will the importance for dececion balance that is at organization since man created by God. Main stage that shall be done by emotional and spiritual quotient is do organizational culture change. Since with revamp organization culture, with its mean with revamps point, trust, assumption, perception, norm, specification, and individual behaviour pattern in organizational eventual one gets to lead organization member in achieving vision and mission that is engaged the problem KPK and POLRI handle. Keywords: Problem KPK-POLRI, emotional and spiritual quotient,